ANALISIS HUBUNGAN LITERASI KESEHATAN TERHADAP PERILAKU PENGELOLAAN OBAT SISA PADA MASYARAKAT KOTA BUKITTINGGI - Suzy Andriyani Sucipto Harjo; Khairil Armal; Tika Afriani (Journal of Science and Clinical Pharmacy Research, 2026)
Health literacy is an important aspect in making health-related decisions, including behaviors in managing leftover medicines. Improper storage and disposal of unused or expired medicines can lead to serious issues such as drug misuse and environmental pollution. This study aimed to determine the relationship between the level of health literacy and leftover medicine management behavior among the community of Bukittinggi City. This research employed an observational analytic method with a cross-sectional design and cluster sampling technique involving 100 respondents. Data were collected using the HLS-EU-SQ10-IDN questionnaire to measure health literacy, along with an additional questionnaire to assess knowledge and behavior regarding leftover medicine management. The results showed that most respondents had a moderate level of health literacy (33.12%), good knowledge (96%), and good management behavior (76%). However, there was no significant relationship between health literacy level and knowledge (p = 0.613) or between health literacy and management behavior (p = 0.253). In conclusion, improving health literacy alone is insufficient to change community behavior in managing leftover medicines. Therefore, specific educational approaches, adequate disposal facilities, and clear household-level pharmaceutical waste regulations are needed to prevent potential health and environmental risks.